Influence of buoyancy on turbulent mixed convection of LBE in a uniform cooled inclined tube. (25th December 2017) - Wang, Yongwei; Xi, Wenxuan; Li, Xunfeng; Huai, Xiulan
Highlights: Turbulent mixed convection of LBE in a cooled inclined tube is investigated. The smaller φ and the larger diameter are helpful to enhance convective heat transfer. The dominant factor effect on convective heat transfer is φ rather than L / d . IHX inclined φ  = 5° can effectively reinforce heat transfer and prevent clogging tube. Abstract: The liquid lead-bismuth eutectic (LBE) is a highly promising coolant for new generation nuclear reactors. The experimental loop is usually arranged inclination or vertical for preventing LBE clogging tube at emergency conditions. Because of the high density and low Prandtl number, LBE natural convection due to buoyancy is significant in the inclined tube. In present work, the influence of buoyancy on LBE convective heat transfer is numerically investigated in a three-dimensional circle tube under different inclined angles and length-to-diameter ratios. The turbulent disturbance resulted from buoyancy reinforces convective heat transfer performances of LBE in the inclined tube. The smaller inclined angle and the larger diameter are helpful to enhance convective heat transfer. The dominant factor effect on convective heat transfer is inclined angles rather than length to diameter ratios. Further numerical investigations of LBE heat exchanger with/without buoyancy are performed. The results indicate that LBE heat exchanger of 5° inclined angle can significantly enhance convective heat transfer with the acceptable pressure drop. This structure is also sufficient to ensure LBE flow back to the storage tank when the pump stops. A reasonable and widely applicable selection criterion of inclined angles is necessary to be constructed to guide engineering applications.